Using numerical procedures to quantify seismic reliability of wood shear walls and braced frames. Issue 9 (September 2016) - Gu, Jianzhong
This article discusses the use of numerical procedures to quantify the probabilistic seismic behaviour of panel-sheathed wood shear walls and diagonally braced frames made with three species including Japanese sugi, Canadian hemlock and European whitewood. Three probabilistic methods were implemented in the analysis, based on the assumption that ground motion records follow a uniform distribution of representing earthquake characteristics. The first method is the traditional one in seismic reliability analysis. The second method calculates the exceeding probability from conditional distributions at given ground motions. The third method is the Monte Carlo simulation method. Confidence curves from two different methods were also used to visualize the comparison among structural configurations and species. The results showed that panel-sheathed walls exhibit better performance than braced frames. The results also show that systems built with hemlock are better than other systems with whitewood or sugi.